Seashore - Parker, Steve; Nang Chan Yeema (New York, USA Alfred A. Knopf, Inc., 1989)
A photo essay introduces the animal inhabitants of the seashore, including fish, crustaceans, snails, and shore birds.
Keywords: Adult Nonfiction